2013
DOI: 10.4183/aeb.2013.97
|View full text |Cite
|
Sign up to set email alerts
|

The p.R16H (C.47G>A) AIP gene variant in a case with invasive non-functioning pituitary macroadenoma and Screening of a Control Cohort

Abstract: Background.Germline aryl hydrocarbon receptor-interacting protein (AIP) mutations are found in familial isolated pituitary adenoma syndrome (FIPA) families and in a small number of sporadic pituitary adenoma (PA) patients. Although the tumorigenic mechanisms of AIP mutations are unclear, truncating mutations are considered pathogenic, but missense mutations are difficult to evaluate. p.R16H (c.47G>A) is a controversial AIP variant of unknown significance.Aim. To describe a new PA case associated with AIP p.R16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…However, despite suggestive data as to the pathogenicity of this AIP variant, it has been regarded as a rare polymorphism (15,18,19), in part due to its detection in unaffected controls (16,18,20), in agreement with the data reported herein and also the lack of co-segregation of the p.Arg16His variant with disease phenotype in some familial cases (21). Of note, results from a recent study regarding p.Arg16His functional impact on AIP protein demonstrated that this alteration is sufficient to disturb cAMP signaling and growth hormone secretion, suggesting that the p.Arg16His variant alone may not be sufficient to produce a pathological effects but along with other mutations may be associated with the pathological mechanism (22).…”
Section: Discussionsupporting
confidence: 88%
“…However, despite suggestive data as to the pathogenicity of this AIP variant, it has been regarded as a rare polymorphism (15,18,19), in part due to its detection in unaffected controls (16,18,20), in agreement with the data reported herein and also the lack of co-segregation of the p.Arg16His variant with disease phenotype in some familial cases (21). Of note, results from a recent study regarding p.Arg16His functional impact on AIP protein demonstrated that this alteration is sufficient to disturb cAMP signaling and growth hormone secretion, suggesting that the p.Arg16His variant alone may not be sufficient to produce a pathological effects but along with other mutations may be associated with the pathological mechanism (22).…”
Section: Discussionsupporting
confidence: 88%
“…While non-functioning adenomas constitute the majority of tumours in patients presenting to our clinic out of the w100-120 new referrals per annum, most such patients fall into an older age group; in this series the majority of patients presented with macroadenomas and a clinical presentation of acromegaly-gigantism rather than non-functioning tumours (24). In our patient group, no AIP variants were identified in any patient other than those with acromegaly; in two cases they were deemed to be definitely pathological, while in another two cases the issue regarding the pathogenicity of the variants is debated (23,25). The missense variant c.47GOA in patient 4 has been described and reviewed recently in the literature in association with an aggressive non-functioning adenoma; our patient showed the clinical picture of a macroadenoma, with aggressive features of increased MIB1 and a sparse granulation pattern.…”
Section: Discussionmentioning
confidence: 80%
“…The pathology demonstrated a sparsely granulated somatotroph macroadenoma with expression of GH staining in 40% of cells. She was found to be heterozygous for missense variant c.47GOA, in exon 1 of AIP, a variant of uncertain pathogenic significance (23).…”
Section: Patientmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the severe clinical, biochemical and imaging picture, our patient did not harbor an AIP mutation (AIP -related pituitary adenomas, frequently somatotroph, either familial or sporadic are usually diagnosed in younger patients and are larger and more invasive) (26).…”
Section: Discussionmentioning
confidence: 71%